Dynamic governance theory for understanding work from home policy: a case of public service in DKI Jakarta during the pandemic / Ahbiiba Nur Iftah Ellahuuta and Putri Faticha Sari - Ellahuuta, Ahbiiba Nur Iftah; Sari, Putri Faticha (2021)
Based on data from the Central Statistics Agency, positive cases of Covid-19 in Indonesia continue to increase and reach 1,252,685 cases on February 18, 2021. It has led to enacting the Work From Home (WFH) policy since March 17, 2020, and remains in place to date. Public service sectors that originally operated offline were required to be online with a significant difference. It causes a decline in performance in some public institutions. The data from Ombudsman reveals that there is an increase in complaints from citizens directed to the public services. As of May 2020, the Ombudsman's total public complaint reached 387 reports. Overall, the several types of reports that dominated were complaints related to social assistance by 72%, finance 23%, transportation and health services 2%, and security by 1%. From the percentage of complaint reports, the Ombudsman obtained data on the areas with the largest number of reports, namely DKI Jakarta, Bogor, Depok, and Bekasi, with a total of 12% or 47 complaints. This research, in turn, attempts to analyze the current shifting from face to face services to technology-based public services in DKI Jakarta. This research uses the dynamic governance theory for understanding the gap between existing.